2016
DOI: 10.5551/jat.32359
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Macrophage Polarization to Metabolic Diseases

Abstract: Macrophage activation is one of the major immunological events in the pathogenesis of various diseases. Recent studies have disclosed that complicated mechanisms are involved in macrophage activation and polarization, and many published research articles have been based on the M1/M2 polarization concept. It is considered that M1-and M2-like macrophages are associated with T helper (Th)1-type and Th2-type immune responses, respectively, via several immune mediators. In this article, we summarize the correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 56 publications
0
44
0
Order By: Relevance
“…In addition, 27HC might contribute towards the stabilization of atherosclerotic plaques. It is considered that there are two broad functional states of macrophages: M1 macrophages, which secrete pro-inflammatory and immune-stimulatory cytokines and are found predominantly in rupture-prone atherosclerosis plaques; while M2 macrophages, which induce myofibroblast activation and release immune-regulatory cytokines, mainly localize in stable plaques [58, 59]. A recent study found that 27HC promotes M2 polarization of human macrophages and exhibits anti-inflammatory effects in vitro , thereby potentially leading to the stabilization of atherosclerotic plaques [60].…”
Section: The Role Of 27hc In Atherosclerosismentioning
confidence: 99%
“…In addition, 27HC might contribute towards the stabilization of atherosclerotic plaques. It is considered that there are two broad functional states of macrophages: M1 macrophages, which secrete pro-inflammatory and immune-stimulatory cytokines and are found predominantly in rupture-prone atherosclerosis plaques; while M2 macrophages, which induce myofibroblast activation and release immune-regulatory cytokines, mainly localize in stable plaques [58, 59]. A recent study found that 27HC promotes M2 polarization of human macrophages and exhibits anti-inflammatory effects in vitro , thereby potentially leading to the stabilization of atherosclerotic plaques [60].…”
Section: The Role Of 27hc In Atherosclerosismentioning
confidence: 99%
“…We also demonstrated that the transcriptional factor Krüppel-like factor (KLF) 15 enhances adipolin expression in cultured adipocytes 51) . TNF-attenuates mRNA expresphages in obese adipose tissue mainly express markers of the M1 or "classically activated" macrophages, which cause exacerbation of inflammation and tissue destruction 44,45) . In contrast, macrophages from lean adipose tissue express markers of the M2 or "alternatively activated" macrophages, which lead to resolution of inflammation and metabolic dysfunction 45) .…”
Section: Adipolin/ctrp12mentioning
confidence: 99%
“…TNF-attenuates mRNA expresphages in obese adipose tissue mainly express markers of the M1 or "classically activated" macrophages, which cause exacerbation of inflammation and tissue destruction 44,45) . In contrast, macrophages from lean adipose tissue express markers of the M2 or "alternatively activated" macrophages, which lead to resolution of inflammation and metabolic dysfunction 45) . Adiponectin deficiency results in increased expression of M1 markers and decreased expression of M2 markers in peritoneal macrophages and the stromal vascular fraction cells of adipose tissue in mice 43) .…”
Section: Adipolin/ctrp12mentioning
confidence: 99%
“…This system demonstrates at least two distinct phenotypes of differentiation: proinflammatory (M1) and anti-inflammatory (M2) 4, 5) . M1 Mφ in atherosclerotic plaques secrete inflammatory cytokines, such as tumor necrosis factor- α (TNF- α ), and promote plaque development and rupture, thereby contributing to the formation of atherothrombosis 6, 7) . Regarding the properties of circulating monocytes, this and other studies previously reported the unfavorable inflammatory balance of M1/M2-like phenotypes of circulating monocytes in obese patients with and without diabetes 4, 8) .…”
Section: Introductionmentioning
confidence: 99%